STANDARDIZATION OF TALISADI CHOORNA AND GUTI CONTAINING SYNTHETIC VANSHLOCHAN - *Atul Gaikwad; Nandini More; Asmita wele (International Journal of Ayurveda and Pharma Research, 2015)
Talisadi choorna and Guti is routinely used in the treatment of Shwas. Vanshlochan is an important ingredient of Talisadi Choorna and Guti. But Vanshlochan has become extinct due to problems in procurement and availability. It is formed only after twelve years of flowering period in hollow internodes of Bamboo. Hence its synthetic substitute is routinely used in Ayurvedic practice and pharmacy. This substitution of natural by synthetic Vanshlochan, whether results in any change in therapeutic activity is not yet known. In Ayurvedic texts preparation of Guti from choorna makes it Laghu and easy to digest is mentioned In the present study analysis of synthetic Vanshlochan was done. X-ray diffraction of synthetic Vanshlochan emitted a blurred peak at 20 degree. This suggests that the sample was amorphous. Surface electron microscopy images were obtained at 10um with resolution of 1000 and 2500. Elemental analysis was done with the help of spot tests, which showed presence of Sodium, phosphorus, potassium. Iron was detected quantitatively with the help of photo-electric calorimeter. Energy dispersive analysis was done in order to confirm the presence of elements detected in chemical analysis. Along with sodium, potassium and phosphorus, other elements like aluminium, silica, calcium, iron, oxygen were detected. In thermogravimetric analysis weight loss of synthetic Vanshlochan was gradual from 37 degree to 610 degree. At 610 degree the weight loss was maximum. From 610 degree to 700 degree, weight of the sample remained constant. This established the thermal stability of the sample at 610 degree. Talisadi choorna was manufactured according to API standards. Values obtained from the quality control tests performed on Choorna were within standard limits. Process of rolling Guti leads to size and weight variation. Hence tablets of the mixture were prepared. For preparation of tablet, mixture was transformed into granules. Magnesium stearate was added to the granules as a lubricant to avoid friction during tableting. As magnesium stearate is an excipient it does not affect therapeutic action of Guti. Values obtained from quality control tests performed on tablets were within standard limits.